SEKOLAH DASAR KONTEMPORER DENGAN FLEKSIBILITAS DAN KONEKTIVITAS RUANG SEBAGAI STRATEGI DESAIN - Martha Paramitha Maeliva; Maria Veronica Gandha (Jurusan Arsitektur dan Perencanaan, 2019)
Information and Communication Technology has always been part of the lives of millennials, generation Z and Alpha, a significant difference in the learning process compared to previous generations. In the current educational environment, the meaning of